Nutritional factors and survival in a cohort of patients with oral cancer - Buscemi, Paolo; Randazzo, Cristiana; Buscemi, Carola; Barile, Anna Maria; Finamore, Elena; Caruso, Roberta; Colombrita, Piero; Lombardo, Martina; Cangemi, Serena; Zucchi, Giulia; Cordova, Adriana; Lo Casto, Antonio; et al. (Frontiers in Nutrition, 2025)
BackgroundMalnutrition commonly affects patients with oral squamous cell carcinoma (OSCC), which contributes to worsening prognosis. Moreover, specific strategies for diagnosing and managing malnutrition in OSCC are lacking. We aimed to investigate if the modality of nutritional treatment as standard oral (ON) or artificial enteral nutrition (AN), assigned by a dedicated nutritional team or not, influences survival in patients with OSCC. Moreover, given the difficulties in obtaining adequate nutritional evaluation in patients with OSCC we preliminary evaluated the magnetic resonance imaging volumetric reconstruction of posterior paraspinal muscles at the level of the third cervical vertebra (MRI-C3) as a tentative new approach to investigate sarcopenia.MethodsThis retrospective study included 52 consecutive patients with OSCC who underwent surgery at the University Hospital of Palermo (I) from Jan 2020 to May 2023. In-hospital nutritional support was provided by a dedicated team. The patients were retrospectively compared with a control group of 11 patients who were surgically treated for OSCC between January and December 2019 in the same unit of surgery, in the absence of a dedicated nutritional team. Upon discharge, the nutritional treatment consisted of ON or AN. In 2020–2023, industrially produced special medical food formulations were used rather than natural foods as it was in use in 2019; also, adequate protein supplements were assigned in order to reach the recommended protein intake of 1–0-1.2 g/kg ideal body weight. The MRI-C3 volumetric reconstruction was obtained in 16 patients.FindingsAs per-protocol, the patients were categorized according to pre-surgery TNM stage: groups A (TNM stages I-III) and B (IVa-IVc). The prevalence of group A patients was 59.6% in the case group and 85.7% in the control group (p < 0.001), with higher survival rates at follow-up in the control group (80.5% vs. 27.3%), therefore, the two historical groups were not comparable. Given the limited number of cases, all patients were included in a unique group. Advanced stages of OSCC (log-rank test, p < 0.001) and AN (p < 0.001) were independently associated with a lower survival rates. The 3–12 month post-surgery MRI_C3 volume increased in patients who received ON treatment and decreased in those who received AN treatment (p < 0.001).ConclusionAN is associated with lower survival probability than ON in patients with OSCC. The MRI-C3 measurement of paravertebral muscles is a promising technique for detecting sarcopenia that needs to be confirmed by further studies including larger groups of patients.